Perencanaan E-Procurement dalam Pengadaan Material Pesawat - Dian Permata Sari (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
With frequent delays in booking aircraft materials carried out in several countries, including: Germany, the United States and France which still use E-Mail in their orders. So the researcher built an E-procurement information system in saturating orders made like a simple tender system. The methodology used in building this E-Procurement information system uses the waterfall methodology as the engineering system stage, namely: Analysis, Designing, cooding, testing and implementation of the system. Whereas the model or tool used in this analytical designer is using UML (Unified Model Language), so the expectation of making this E-Procurement information system is to assist the procurement of aircraft materials in meeting the needs of the procurement of materials in warehouses with good material quality cheap and non-miss communication on orders.